Macroplastic pollution in mangrove forests of Tangub City, Panguil Bay, Philippines - LESLIE SAM L. PACULBA; RIALONA CHRISTINE AN C. MABIDA; GENECA CLAIRE M. PERICO; EDUARDO D. MAGDAYO JR.; FRANK T. ACOT JR. (Nusantara Bioscience, 2024)
Abstract. Paculba LSL, Mabida RCAC, Perico GCM, Magdayo Jr ED, Acot Jr FT. 2024. Macroplastic pollution in mangrove forests of Tangub City, Panguil Bay, Philippines. Nusantara Bioscience 16: 251-262. Plastic pollution poses a growing threat to coastal ecosystems. In the Philippines, studies on macroplastic pollution in mangrove forests are limited. This study was therefore conceptualized to assess the extent of macroplastic litter in the mangrove forests of Tangub City, Misamis Occidental, Philippines. The objectives encompassed on determining the count, composition, weight, and polymer type of collected macroplastics, quantifying and comparing the density of macroplastic litter, assessing the clean-coast index, and investigating the impacts of macroplastic litter in mangrove forests. A 50-meter transect line perpendicular to the shore with three 10m×10m quadrats was delineated in the sampling areas. Macroplastic litter collection was done during eight non-consecutive days in in September-October 2023. Results found that Sonneratia alba Sm. with its aerial root structure dominated in San Apolinario trapped more plastics. Food packaging accounted for 48.7% of the composition, with Low-Density Polyethylene (LDPE) being the most common polymer type at 44%. The highest macroplastic density was 0.20 items/m² for San Apolinario. While plastic density varied across sites despite similar cleanliness ratings, the distribution remained consistent throughout the mangrove forests indicating no significant differences in areas (p=.45). Moreover, findings showed that plastic litter harmed the mangrove forests as the pneumatophores were smothered, the branches were twisted, and the stems were damaged disrupting the mangroves' structure. This study highlights the importance of understanding plastic pollution in mangroves to develop effective waste management and conservation strategies.